Peri-operative nurses' knowledge and reported practice of pressure injury risk assessment and prevention: A before-after intervention study - Sutherland-Fraser Sally; McInnes Elizabeth; Maher Elizabeth; Middleton Sandy (BMC, 2012)
Abstract Background Patients are at risk of developing pressure injuries in the peri-operative setting. Studies evaluating the impact of educational interventions on peri-operative nurses' knowledge and reported practice are scarce. The purpose of this study was to evaluate the effect of a multifaceted intervention on peri-operative nurses' (a) knowledge of pressure injury risks, risk assessment and prevention strategies for patients in the operating suite; and (b) reported practice relating to risk assessment practices and implementation of prevention strategies for patients in the operating suite. Methods A before-after research design was used. A convenience sample of all registered and enrolled nurses employed in two hospitals' operating suites was recruited. A multifaceted intervention was delivered which comprised a short presentation, educational materials and reminder posters. A 48-item survey tool was completed pre-and post-intervention to measure self-reported knowledge and practice. Results 70 eligible peri-operative nurses completed both surveys. Post-intervention, statistically significant improvements were seen in knowledge of correct descriptions of pressure injury stages (p=0.001); appropriate reassessment for patients with a new pressure injury (p=0.05); appropriate actions for patients with an existing stage 1 (p=0.02) and stage 2 pressure injury (p=0.04). Statistical improvements were also seen in reported practice relating to an increase in the use of a risk assessment tool in conjunction with clinical judgement (p=0.0008); verbal handover of patients' pressure injury risk status from the operating room nurse to the recovery room (p=0.023) and from the recovery room nurse to the postoperative ward nurse (p=0.045). The number of participants reporting use of non-recommended and recommended pressure-relieving strategies was unchanged. Conclusion A multi-faceted educational intervention can improve some aspects of perioperative nurses' knowledge and reported practice such as risk assessment practices but not others such as use of recommended pressure-relieving devices. Further research is required to ascertain effective interventions which improve all areas of practice and knowledge, particularly in the use of appropriate pressure-relieving devices in order to prevent pressure injuries in surgical patients.